Relapsing endocarditis caused by Enterococcus faecalis forming small colony variants. (October 2013) - Benes, Jiri; Dzupova, Olga; Setina, Marek; Feuereisl, Rudolf; Svec, Pavel; Pantucek, Roman
Abstract Small colony variants (SCVs) are subpopulations of a bacterial strain that differ in morphology, growth rate, metabolism, and antibiotic sensitivity from the parent line. They are associated with chronic and difficult-to-treat infections. SCV endocarditis is very rare and usually associated with intracardiac devices. Herein, we report a case of endocarditis caused by SCV-forming Enterococcus faecalis that affected the native heart without any known predisposition.